Work in shipping industry: An exploratory study of Marine Engineers in Merchant Navy - Vyasapeetam, Divya (2008)
Marine Engineering as a profession is widely recognised but very little is known about the people who do the work. Through this project, I have analysed the various aspects of a Marine Engineer‟s profession, tried to explore the nature of the job done by them and also tried to uncover their reasons and preferences in choosing to continue in their profession. This study also throws light on their attitudes towards their companies and its HR policies, their satisfaction/ discontentment in this area. Interviews with Marine Engineers were used to gather information useful to this research.